"THE ROLE OF INACTIVE PITUITARY ADENOMAS IN THE DEVELOPMENT OF GONADOTROPIC HYPOGONADISM IN WOMEN: BIOLOGICAL AND HORMONAL FEATURES" (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The article discusses the role of inactive pituitary adenoma in the development of hypogonadotropic hypogonadism in women. Clinical manifestations and hormonal changes were studied in 76 patients aged 18 to 47 years. It was found that hypogonadotropic hypogonadism is the most common clinical manifestation of pituitary insufficiency (67%) in tumors of the chiasmal-sellar region. The main symptoms include menstrual irregularities, infertility, neurovegetative and urogenital disorders, as well as uterine and ovarian hypoplasia. Symptoms of hypogonadism appear in the early stages of the disease, before the development of visual and neurological disorders. The diagnosis is confirmed by a decrease in the levels of LH, FSH and estradiol.